Following the wind (跟风): navigating Chinese durian farmers' identity and practices in Balik Pulau, Penang - Wong, Penny Pui Yan (2024)
For generations since the mid-19th century, the Hakka Chinese have settled on the hills of Balik Pulau, the quiet backwaters of Penang Island. They ‘followed the wind’ as pragmatic smallholder farmers to cultivate the land, growing nutmeg and cloves as well as seasonal tropical fruits. Today, many of them are durian farmers whose grandfathers and fathers pioneered the durian industry in Penang and introduced well-known Penang varieties like Kun Poh, Red Prawn, Green Skin 15, 604, and others to Malaysia and beyond. This thesis aims to explore the Balik Pulau durian industry through the lens of durian farmers’ practices who are predominantly Hakkas. Employing practice theory as the theoretical framework, data gathered from in-depth semi-structured interviews and field observation on durian farms reveal that their practices have transitioned throughout the 1950s to the 2020s. This transition can be categorised into three phases: the genetic experimentation of durians, the narrowing and standardisation of durian varieties, and the marketing and sales of durians through value-added services. These phases demonstrate the reconstruction of the durian farmers’ socio-cultural identity: from farmer to agropreneur. Most durian farmers find little to no occupational affinity between being a Hakka person and agricultural work, signifying a low level of Chinese speech group consciousness. Instead, their socio-cultural identity is primarily shaped through their daily activities and improvisation of practices on the farm. The creativity and improvisation of their early work in the 1950s played a crucial role in the initial growth of the durian industry in Balik Pulau, paving the way for the emergence of the current durio-tourism scene in Penang today. Durio-tourism highlights durian diversity, representing the Hakka durian farmers’ drive for innovation. This is evident in their efforts to breed various durian varieties and adapt to modern resources to enhance yield. This distinguishes them from durian farmers from other states, who focus on exporting predominantly Musang King to China. In Penang, tourists from China are taught to widen their palate and taste different types of durians apart from Musang King. The durian farmers regard their roles not just as farmers, but as cultural ambassadors of Penang durians in the tourism industry.